The impact of fiscal policy on macroeconomic variables in Iraq A standard analytical study for the period (2003-2020) - HUSSEIN, BAYDAA (The Gulf Economist, 2022)
The difficulty of the task that falls on the shoulders of fiscal policy, made it fall into the circle of contradiction between achieving economic efficiency and distributive justice, and its focus often on the latter, has made it lose the ability to create a solid base through the element of efficiency to achieve the second goal, and in a way that paves the way To build a model for renter countries that seek to achieve efficiency and justice together, and that is to reach a level in which the process of distributing oil revenues flows through the general budget, achieving economic stability. Macroeconomics, the research followed the descriptive-analytical approach and the standard approach to describe and analyze the variables affecting the model and test the statistical significance of the model variables. The exchange rate and the increase in the value of the local currency, thus increasing economic growth, with the need to focus public expenditures in all aspects development and capitalism in order to increase the productive value, which is reflected in increasing output and reducing inflation rates.